Change of CRP and D-dimer Level of COVID-19 Patients: An Observational Prospective Study (Chest & Heart Journal, 2023)
Background: COVID-19 is a global pandemic causing million of death during last two years, so it became a global health and economic burden right now. COVID-19 is a Novel infectious disease, for which there is no definite curable treatment till now. It is therefore necessary to explore biomarkers to determine the extent of lung lesions and disease severity. CRP levels are elevated in patients with COVID-19 and may be different with severity of the disease. Elevated plasma Ddimer is a hallmark to determine cardiovascular complications related to patients.Objective: The primary objective of the present study was to evaluate the changes of CRP and D-dimer level of COVID-19 patients in respect to severity of the disease.Methods: This prospective observational study was conducted in Private set up and OPD, National Institute of Diseases of the Chest & Hospital, Mohakhali, Dhaka, between January 2020 to July 2020. A total of 49 patients with COVID-19 were included in the study. Diagnosed case of RT-PCR positive patients with or without respiratory symptoms were assessed by CRP and D-dimer level on the first visit. After 7 days CRP and D-dimer levels were collected to compare with baseline levels. All other clinical, laboratory, and outcome data were documented using a standardized data collection form.Results: In this study 49 patients with COVID-19, majority 22(44.9%) patients belonged to age 41 to 60 years. The mean age was 53.3±14.7 years. Male patients were predominant 41(83.7%) with male female ratio was 5.1:1. More than one third 17(34.7%) patients had hypertension followed by 15(30.6%) had diabetes mellitus, 4(8.2%) had COPD, 3(6.1%) had asthma and 2(4.1%) had CKD. Co-morbidity was significantly higher in respiratory symptoms than without respiratory symptoms. CRP level was significantly reduced after 7 days compared with baseline (10.1±13.0 mg/L vs39.6±54.6 mg/L). Twenty three (46.9%) patients were found D-dimer >3.0 gm/dl in baseline and 14(28.6%) in after 7 days, that was not significant (p=0.066).Conclusion: At the early stage of COVID-19, CRP levels were positively correlated with lung lesions. Co- morbidity was significantly associated with respiratory symptoms. This study found significant reduced CRP levels after 7 days compared with baseline. D-dimer levels also reduced but not significant. CRP levels and D-dimer could reflect disease severity and should be used as a key indicator for disease monitoring.Chest Heart J. 2021; 45(1) : 19-25